Análisis de factibilidad para la implementación de un sistema ERP para la gestión de los procesos de ventas para la Empresa "Su Economía " ubicado en la parroquia el salto del cantón Babahoyo. - Bravo Martínez, Geomayra Estefanía (2022)
The company "Su Economía" is a commercial company dedicated to the purchase and commercialization of basic necessities, dairy products, fruits, vegetables, and beverages. Providing an added cost to its commercial by applying a neighborhood bank service for the convenience of customers. It is located in the parish of El Salto on Malecón Avenue and Third Avenue in the city of Babahoyo. In addition, it was learned that their commercial activities began on October 22, 2016. This research was conducted in order to conduct a comprehensive study, which allows, through various analytical tools, to identify the different problems that arise in sales management, so as to determine how feasible is the implementation of an ERP system, through this tool has is intended to better optimize processes, in order to reduce the cost of information management, for this reason, the final implementation of the ERP system will contribute significantly to increase the productivity of the company. In the finalization of the case study, it was possible to determine several problems arising in the environment of the company and all this was thanks to the analysis of the results of the methodologies and research tools applied. In which it was possible to conclude that the implementation of an ERP system is necessary to provide a solution to the company's problems. With the results obtained from the technical feasibility study, it was determined which technological resources the company must have in order to implement the project. It should be noted that thanks to the results obtained from the economic feasibility study, it was concluded that the execution of this project does not require investment, and it is economically feasible.